Race and the Houston police department, 1930-1990 : a change did come - Watson, Dwight (Centennial series of the Association of Former Students, Texas A & M University, 2005)
Examines the racial history of the Houston Police Department, drawing on police records and contemporary accounts to look at how Houston, and other police departments, responded to social, political, and institutional change from 1930 to 1990.